Assessment of the neurotoxicity of oral dihydroartemisinin in mice. - Nontprasert, A; Pukrittayakamee, S; Prakongpan, S; Supanaranond, W; Looareesuwan, S; White, N (2002)
High doses of the oil-soluble antimalarial artemisinin derivatives artemether and arteether, given by intramuscular injection to experimental mammals, produce an unusual pattern of selective damage to brainstem centres predominantly involved in auditory processing and vestibular reflexes. We have shown recently, in adult Swiss albino mice, that constant exposure either from depot intramuscular injection of oil-based artemisinin derivatives, or constant oral intake carries relatively greater neurotoxic potential than other methods of drug administration. Using the same model, oral dihydroartemisinin suspended in water was administered once or twice daily at different doses ranging from 50 to 300 mg/kg/day for 28 days. The neurotoxic potential of the oral dihydroartemisinin was assessed and compared to that of oral artemether and artesunate. Oral artemether, artesunate, and dihydroartemisinin had similar neurotoxic effects with no significant clinical or neuropathological evidence of toxicity at doses below 200 mg/kg/day. These data indicate that once and twice daily oral administration of artemether, artesunate and dihydroartemisinin is relatively safe when compared to intramuscular administration of the oil-based compounds.